Laboratory Techniques In Lingual Orthodontics - Yıldız Öztürk-Ortan (Galenos Yayinevi, 2008)
If the brackets are not well positioned before the orthodontic treatment it's obvious that the treatment time will increase and the final results may not be satisfactory. Because of the difficulty in access and wide anatomical variation of the lingual surfaces of the teeth it is not possible to place the lingual brackets on their ideal positions. These conditions makes indirect bonding an essential procedure for lingual orthodontics. In this review the laboratory procedures where the lingual brackets are placed on the original or on the duplicated set-up dental models are summarized.